2023
DOI: 10.1021/acs.inorgchem.3c02467
|View full text |Cite
|
Sign up to set email alerts
|

Motif-to-Core Nucleation in a Decahedral Evolution Pattern

Xiangyu Ma,
Shuping He,
Qingliang Li
et al.

Abstract: The atomic precision of ultrasmall metal nanoclusters has opened the door to elucidating the structural evolution principles of metal nanomaterials at the molecular level. Here, we report a novel set of super-atomic Ag clusters, including [Ag19(TBBT)16(DPPP)4]+ (Ag19), [Ag22(DMAT)8(DPPM)4Cl8]2+ (Ag22), Ag26(SPh3,5‑CF3)15(DPPF)4Cl5 (Ag26), and [Ag30(DMAT)12(DPPP)4Cl8]2+ (Ag30). The core structures of these clusters correspond to one decahedral Ag7, perpendicular bi-decahedrons, three-dimensional penta-decahedro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…By employing various combinations of thiol and diphosphine, a rare collection of super-atomic Ag NCs with sizes Ag 19 , Ag 22 , Ag 26 , and Ag 30 , possessing 2, 4, 6, and 8 free valence electrons respectively, has been reported. 37 Interestingly, the cores of these clusters consist of one decahedral Ag 7 , perpendicular bidecahedra, three-dimensional penta-decahedra, and hexadecahedra, respectively. The strong structural correlation demonstrates the motif-to-core evolution of the surface Ag (on AgS 2 ) to construct additional decahedral blocks, offering opportunities to investigate the impact of decahedral evolution patterns on the properties of NCs.…”
Section: Synthetic Strategiesmentioning
confidence: 99%
“…By employing various combinations of thiol and diphosphine, a rare collection of super-atomic Ag NCs with sizes Ag 19 , Ag 22 , Ag 26 , and Ag 30 , possessing 2, 4, 6, and 8 free valence electrons respectively, has been reported. 37 Interestingly, the cores of these clusters consist of one decahedral Ag 7 , perpendicular bidecahedra, three-dimensional penta-decahedra, and hexadecahedra, respectively. The strong structural correlation demonstrates the motif-to-core evolution of the surface Ag (on AgS 2 ) to construct additional decahedral blocks, offering opportunities to investigate the impact of decahedral evolution patterns on the properties of NCs.…”
Section: Synthetic Strategiesmentioning
confidence: 99%
“…7–21 It has been observed that the metal core of many of these clusters shares the same polyhedral units, despite variations in peripheral ligands or metal–ligand motif structures. These polyhedral units encompass an M 13 centered icosahedron, 22–28 an M 6 octahedron, 29–35 an M 13 cuboctahedron 36 and an M 7 decahedron, 37–42 among others, where ‘M’ represents Au, Ag, Cu, or other metal atoms or their mixtures. These fundamental polyhedral units can also be assembled through the sharing of vertices, edges, or faces, expanding the range of structural types for clusters.…”
Section: Introductionmentioning
confidence: 99%
“…However, the systematic research of the substituent influence on the optical properties and excited state dynamics is still lacking, which is important for constructing emission-specific metal nanoclusters. 11,16,17…”
mentioning
confidence: 99%